(untitled) (Latakia University Journal -Medical Sciences Series, 2021)
This study aims to prepare diclofenac sodium extended-release tablets by using film coating technique due to the various advantages of extended-release dosage forms. Several formulas have been prepared using Ethyl-cellulose as a polymer at a concentration of 5% in alcohol. The different properties of granules and tablets (before and after coating) were evaluated. The effect of different factors of coating on the release of diclofenac sodium from the coated tablets was studied, such as the effect of the thickness of the coating, the plasticizer (silicone oil) and its concentration, the presence and type of filler (talc or magnesium stearate). The results showed that the release of diclofenac sodium was decreased by increasing the thickness of the coating layer; the presence of hydrophobic plasticizer, by increasing its concentration and with the presence of hydrophobic filler. Diclofenac sodium released by relaxation and diffusion mechanisms and according to Higuchi model in most formulations.